TEACHING SIMPLE PRESENT TENSE THROUGH COLLABORATIVE WAYS: INDUCTIVE INSTRUCTION AND LOCAL CONTENT BASED LESSON AT THE FIRST SEMESTER STUDENTS - Tiwery, Yulina; Sairiltiata, Sefanya; Anidlah, Apriliani D. (Jurnal Review Pendidikan dan Pengajaran, 2023)
This research aimed to find out whether the implementation of Inductive Instruction and Local Content Based Lesson as the collaborative way in teaching Simple Present Tense (SPT) was effective or not. The research was done at English Education Study Program at the first semester students who took Grammar in Written Discourse Subject with one to one class pretest-posttest. The instruments were the result of pretest and posttest consisted of 20 numbers of multiple-choice questions. The researchers analyzed the data through SPSS application. The researchers found that, the percentage of mean N gain score is 76.52% which is more than 76% the standard percentage of interpretation data and the mean score in pre-test (50.57) and post-test is (87.50). To see how effective these ways to teach Simple Present Tense and also to prove the result of hypotheses testing, the researchers used the result of Sig 2-tailed. It is obtained that the value sig 2-tailed (0,000) is less than the value of . So, finally, Ho is rejected and Ha is accepted.